Innovation Of Administrative Services In Pemurus Village In South Banjarmasin Sub-District, Banjarmasin City - Suriyani, Erna; Umi Hawa, Nurul; Lutnah, Sarifah; Ilma, Aulia (International Journal of Educational Research & Social Sciences, 2024)
This research aims to find out about the innovation of administrative services in Pemurus Village in South Banjarmasin District, Banjarmasin City. Innovation in research is defined as a planned change in the form of ideas, ideas, new objects/objects or technology and the use of new equipment within the scope of government agencies, namely urban village. The type of research used is a descriptive study with a qualitative approach. The findings in the study are that Pemurus Dalam Village participates in innovating administrative services with the siPalui Application, namely Palui Mobile, which can be accessed by residents to get mail services in all urban villages in Banjarmasin city only through Smartphones, instagram and whatsApp. The existing facilities are quite good and the condition of the village office is comfortable and clean and the office employees are ready to serve the community who want to take care of administration/certificates and others. This readiness is also stated in the instagram account of the village office and a whatsApp number has been provided to communicate which means that the Village Management has carried out delivery innovations. However, this application often experiences network disruptions so that village employees cannot run the application and also for a while the application cannot be accessed due to application updates and application system maintenance.